2009
DOI: 10.1155/2009/870323
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Malignancy and Recommended Follow-Up for Patients with Negative Endoscopic Ultrasound-Guided Fine-Needle Aspiration of Suspected Pancreatic Lesions

Abstract: For patients undergoing EUS-FNA for a suspected pancreatic lesion, a negative or nondiagnostic FNA does not provide conclusive evidence for the absence of cancer. Patients for whom vascular invasion and lymphadenopathy are detected on EUS are more likely to have a true malignant lesion and should be followed closely. When a patient has been monitored for six months or more with no cancer being diagnosed, there appears to be much less chance that a pancreatic malignancy is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Negative results of pancreatic US-FNA, therefore, should be viewed with caution, and radiological and clinical findings should be always taken into account during cytologic examination. In this regard, a study by Spier et al [18] suggested that in patients with a definite solid lesion with imaging features suspicious for malignancy such as invasion of the adjacent vessels or the presence of peripancreatic lymph nodes-despite negative FNA-the FNA result should be considered as false negative FNA, and the patients followed closely, with an early repeat attempt at tissue acquisition and repeat imaging, or strongly considered for direct referral for an intra-operative sample. Moreover, these authors reported that in the majority of patients with a false-negative FNA who were diagnosed with cancer, the diagnosis was made within 90 days after FNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative results of pancreatic US-FNA, therefore, should be viewed with caution, and radiological and clinical findings should be always taken into account during cytologic examination. In this regard, a study by Spier et al [18] suggested that in patients with a definite solid lesion with imaging features suspicious for malignancy such as invasion of the adjacent vessels or the presence of peripancreatic lymph nodes-despite negative FNA-the FNA result should be considered as false negative FNA, and the patients followed closely, with an early repeat attempt at tissue acquisition and repeat imaging, or strongly considered for direct referral for an intra-operative sample. Moreover, these authors reported that in the majority of patients with a false-negative FNA who were diagnosed with cancer, the diagnosis was made within 90 days after FNA.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond 3 months post-FNA, if a patient has not been diagnosed with cancer despite clinical suspicion or imaging findings, it is unlikely that the patient has an underlying malignancy that was missed at the time of FNA. Thus, after a negative FNA in patients who do not have suspicious imaging findings, it is reasonable to perform one or two follow-up CT/MRI examinations in the first 3-6 months after a negative FNA, but longer-term surveillance is rarely needed [18].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the results, all the patients should be followed for more than 6 months. 24 Moreover, routine use of cytology and microhistology in association with EUS-FNA lead to the preoperative description of various pancreatic masses: neuroendocrine tumors and metastases (eg, melanoma, renal cell carcinoma) as well as other rare tumors of the pancreas (eg, lymphoma, small cell carcinoma, angiomyolipoma, solid pseudopapillary tumors). [27][28][29][30][31][32] Previous studies clearly showed that pancreatic adenocarcinoma is a relatively hypovascular tumor, although more than 65% of the patients have detectable vessels inside.…”
Section: Discussionmentioning
confidence: 99%
“…7 This does present some problems when viewed through the filter of recent understanding. This is especially true when considering entities with variable malignant potential including mucinous cystic lesions [8][9][10] and neuroendocrine tumors. In this program, a mucinous cystic neoplasm corresponded to samples with extracellular mucin and morphologically benign mucinous epithelial cells.…”
Section: Methodsmentioning
confidence: 99%